2005
DOI: 10.1038/sj.bjc.6602655
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic relevance of activated extracellular-regulated kinases (ERK1/2) in breast cancer

Abstract: Extracellular-regulated kinases (ERK1, ERK2) play important roles in the malignant behaviour of breast cancer cells in vitro. In our present study, 148 clinical breast cancer samples (120 cases with follow-up data) were studied for the expression of ERK1, ERK2 and their phosphorylated forms p-ERK1 and p-ERK2 by immunoblotting, and p-ERK1/2 expression in corresponding paraffin sections was analysed by immunohistochemistry. The results were correlated with established clinical and histological prognostic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 30 publications
11
57
1
2
Order By: Relevance
“…Proteins were lysed in ice-cold sample buffer (50 mM Tris pH 6.8, 1% sodium dodecyl sulphate (SDS), 10% sucrose and 10 ml ml À1 protease inhibitor cocktail (Sigma, Taufkirchen, Germany)), and protein concentration was determined following the standard protocols and using bovine serum albumin protein standards as described previously (Bamberger et al, 1999;Milde-Langosch et al, 2005).…”
Section: Protein Extractionmentioning
confidence: 99%
“…Proteins were lysed in ice-cold sample buffer (50 mM Tris pH 6.8, 1% sodium dodecyl sulphate (SDS), 10% sucrose and 10 ml ml À1 protease inhibitor cocktail (Sigma, Taufkirchen, Germany)), and protein concentration was determined following the standard protocols and using bovine serum albumin protein standards as described previously (Bamberger et al, 1999;Milde-Langosch et al, 2005).…”
Section: Protein Extractionmentioning
confidence: 99%
“…Particularly, deregulated kinases are often found to be oncogenic and can be central for the survival of cancer cells (Hunter and Cooper 1985). Moreover, the phosphorylation of some proteins, such as ErbB2 (Cicenas et al 2006;Cicenas 2007;DiGiovanna et al 2005), EGFR (Cicenas 2007;Kanematsu et al 2003), Erk (Milde-Langosch et al 2005;Bergqvist et al 2006;Svensson et al 2005), SchA (Cicenas et al 2010), p21Cip1 (Xia et al 2004), p27Kip1 (Clarke 2003), Akt (Cicenas et al 2004(Cicenas et al , 2005Cicenas 2008) and retinoblastoma protein (Rb) (Derenzini et al 2007), is associated with prognosis in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Much of the current literature that lends support for ERK-1/2 serving as a cancer driver has been generated by the use of in vitro, ex vivo, and mouse cancer models, with an actual paucity of studies that report its expression, activity, and significance in clinical tumor specimens. 21 Of the clinical immunohistologic studies undertaken to date, phosphorylated ERK (pERK) has been shown to correlate with disease progression in melanoma, 22 hepatocellular, 23 and nonsmall cell lung carcinomas. 24 In hepatocellular carcinoma, pERK is predominantly expressed in poorly differentiated tumors, and as such serves as a powerful prognostic factor.…”
mentioning
confidence: 99%